2012
DOI: 10.3390/molecules17077810
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning, Characterization and Expression of the Phenylalanine Ammonia-Lyase Gene from Juglans regia

Abstract: Phenylalanine ammonia-lyase (PAL) is the first key enzyme of the phenypropanoid pathway. A full-length cDNA of PAL gene was isolated from Juglans regia for the first time, and designated as JrPAL. The full-length cDNA of the JrPAL gene contained a 1935bp open reading frame encoding a 645-amino-acid protein with a calculated molecular weight of about 70.4 kD and isoelectric point (pI) of 6.7. The deduced JrPAL protein showed high identities with other plant PALs. Molecular modeling of JrPAL showed that the 3D m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
73
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(84 citation statements)
references
References 50 publications
8
73
1
2
Order By: Relevance
“…Some highly conserved residues were found in the , Q 497 and 3, 5-dihydro-5-methylidene-4H-imidazol-4-one (MIO), which were considered to be of significant importance for substrate binding, catalytic activity and LMIO formation (Xu et al, 2008). The mechanism was in agreement with the recent report from Petroselinum crispum research (Röther et al, 2002).…”
Section: Cytologic Characterization and Function Domain Investigationsupporting
confidence: 80%
“…Some highly conserved residues were found in the , Q 497 and 3, 5-dihydro-5-methylidene-4H-imidazol-4-one (MIO), which were considered to be of significant importance for substrate binding, catalytic activity and LMIO formation (Xu et al, 2008). The mechanism was in agreement with the recent report from Petroselinum crispum research (Röther et al, 2002).…”
Section: Cytologic Characterization and Function Domain Investigationsupporting
confidence: 80%
“…This gene was previously characterized and designated as JrPAL (Xu et al 2012a). Expression of the transcription factor gene JrCBF was also studied .…”
Section: Progress On Transcriptomicsmentioning
confidence: 99%
“…CCC treatments also significantly induced the activities of PAL, CHS, and CHI in a concentration-dependent manner in ginkgo leaves. Recent findings demonstrated that PAL, CHS and CHI were both key regulatory enzymes in flavonoid biosynthesis in G. biloba leaves Xu et al, 2007Xu et al, , 2008 and observed that CCC could induce the transcription of chalcone isomerase gene (GbCHI) in ginkgo leaves . The transcript levels of several genes encod-…”
Section: Discussionmentioning
confidence: 99%